Pricing Intermittent Renewable Energy - Stefan Ambec; Claude Crampes; Stefan Lamp (CESifo GmbH, 2025)
The energy transition requires significant investment in intermittent renewable energy sources, such as solar and wind power. New generation capacities are generally procured through fixed price contracts, such as power purchase agreements and contracts for difference, or feed-in tariffs. With these designs, renewable technologies are selected based on their generation, regardless of their adequacy with demand and supply by other technologies. We show that fixed-price contracts implement the optimal portfolio of renewable technologies if the price is adjusted with a technology-specific bonus-malus system that depends on the correlation between renewable energy production and the wholesale electricity price. We estimate the bonus-malus for solar and wind power in California, France, Germany, and Spain and decompose it to identify the key market factors driving the adjustment. We argue that the bonus-malus measures the cost of integrating intermittent generation into the energy mix. Therefore, it should be added to the levelized cost of energy (LCOE) to obtain the cost of generating an additional megawatt-hour with a specific renewable technology.
Keywords: D47; L23; Q41; Q48; 330; electricity market; levelized cost of energy; climate change; intermittent renewable energy; feed-in tariff; power purchase agreement; contract for difference